Management Challenges and Potential Malabsorption of Valproic Acid in a Patient with Bipolar Disorder and Gastrointestinal History - James Kwok; Janeline Wong; Kye Kim (Case Reports in Psychiatry)
Bipolar disorder is a chronic psychiatric condition typically managed using mood stabilizers such as valproic acid, lithium, and atypical antipsychotics, the former which is absorbed in the gastrointestinal tract. This case report presents the challenges encountered in managing bipolar disorder in a patient with a history of extensive gastrointestinal (GI) issues. The patient was initially treated with lithium but experienced adverse effects, prompting a switch to valproic acid (VPA) tablets. However, due to ongoing GI problems unrelated to her medication and to help improve tolerability, the patient underwent multiple medication formulation changes, including Depakote delayed release tablets, Depakene liquid, and Depakote sprinkle capsules. However, the patient’s VPA levels decreased below therapeutic levels after the formulation changes despite medication compliance. This case highlights the importance of considering GI issues in optimization of a treatment plan for patients with bipolar disorder.